Admission avoidance hospital at home - Shepperd, S; Iliffe, S; Doll, HA; Clarke, MJ; Kalra, L; Wilson, AD; Gonçalves-Bradley, DC (Cochrane Collaboration, 2016)
Background Admission avoidance hospital at home provides active treatment by healthcare professionals in the patient's home for a condition that otherwise would require acute hospital inpatient care, and always for a limited time period. This is the third update of the original review.